Blood-borne markers of fatigue in competitive athletes - Results from simulated training camps - Hecksteden, A.; Skorski, S.; Schwindling, S.; Hammes, D.; Pfeiffer, M.; Kellmann, M.; Ferrauti, A.; Meyer, T. (PLOS ONE, 2016)
Assessing current fatigue of athletes to fine-tune training prescriptions is a critical task in competitive sports. Blood-borne surrogate markers are widely used despite the scarcity of validation trials with representative subjects and interventions. Moreover, differences between training modes and disciplines (e.g. due to differences in eccentric force production or calorie turnover) have rarely been studied within a consistent design. Therefore, we investigated blood-borne fatigue markers during and after discipline-specific simulated training camps. A comprehensive panel of blood-born indicators was measured in 73 competitive athletes (28 cyclists, 22 team sports, 23 strength) at 3 time-points: after a run-in resting phase (d 1), after a 6-day induction of fatigue (d 8) and following a subsequent 2-day recovery period (d 11). Venous blood samples were collected between 8 and 10 a.m. Courses of blood-borne indicators are considered as fatigue dependent if a significant deviation from baseline is present at day 8 (Delta fatigue) which significantly regresses towards baseline until day 11 (Delta recovery). With cycling, a fatigue dependent course was observed for creatine kinase (CK; Deltaf atigue 54±84 U/l; Deltarecovery -60±83 U/l), urea (Delta fatigue 11±9 mg/dl; Delta recovery -10±10 mg/dl), free testosterone (Delta fatigue -1.3±2.1 pg/ml; Delta recovery 0.8±1.5 pg/ml) and insulin linke growth factor 1 (IGF-1; Delta fatigue -56±28 ng/ml; Delta recovery 53±29 ng/ml). For urea and IGF-1 95% confidence intervals for days 1 and 11 did not overlap with day 8. With strength and high-intensity interval training, respectively, fatigue-dependent courses and separated 95% confidence intervals were present for CK (strength: Delta fatigue 582±649 U/l; Delta recovery -618±419 U/l; HIIT: Delta fatigue 863±952 U/l; Delta recovery -741±842 U/l) only. These results indicate that, within a comprehensive panel of blood-borne markers, changes in fatigue are most accurately reflected by urea and IGF-1 for cycling and by CK for strength training and team sport players.